Passeios pedagógicos: uma análise das potencialidades educativas das visitas a museus na compreensão dos alunos do ensino fundamental II - Silva, Caio Henrique Silveira da (2019)
This investigation considers the idea of educational processes as part of social environments. Through this point of view, we have the understanding of museums as places where knowledge and the sense of era are approached, transposing to the pedagogical area a rich multidisciplinary environment, resulting in its use as a tool for the enlargement of students cultural background. The objective for this research is to analyze educational potentialities which were observed during the visits to the museums, based on the understanding of middle school students. For this qualitative research, we considered the methodology of a case study, in order to understand and emphasize its singularities, which is, in this case, the pedagogical visits provided by SME, in São Carlos. The data were gathered through forms which were distributed to 124 6th grade students. The results show a variety of meaningful knowledge, either part of the curriculum or extracurricular, which enlarges their cultural capital and spread the museologic culture.